(untitled) (REMUNOM, 2024)
This paper focuses on corporate liability in execution proceeding in a labor court, examining the conditions under which a company’s shareholders may be held responsible for unpaid labor debts. The objective is to analyze the grounds and limits of this liability, with an emphasis on the application of the disregard of legal entity doctrine and the distinction between joint and subsidiary liability. The relevance of this study lies in the importance of protecting labor credits, which are essential for workers’ subsistence and should take priority, as well as addressing the rise in cases where companies, acting in bad faith, attempt to evade their labor obligations. The methodology employed is a literature review encompassing doctrines, legislation, and case law governing labor enforcement and shareholder liability. The analysis included provisions from the Civil Code, Consolidation of Labor Laws (CLT), Consumer Protection Code, as well as procedural norms and judicial precedents. The findings show that labor courts, by allowing the piercing of the corporate veil in cases of abuse or fraud, reinforce the enforcement of labor rights. It was also observed that the application of the major and minor disregard theories depends on the specifics of each case, with courts adopting flexible approaches to protect workers while maintaining legal certainty.